(untitled) (JBIOEDRA: Jurnal Pendidikan Biologi, 2025)
Traditional knowledge of medicinal plants is an essential part of local wisdom that needs to be preserved and integrated into biology education. However, in the era of modernization, this knowledge is increasingly marginalized and rarely documented systematically, which may lead to its gradual disappearance. This study aimed to explore the types of medicinal plants used by the Weol community in Wae Belang Village, Ruteng District, Manggarai Regency, and to develop them into a biology learning medium in the form of a booklet. The research was conducted in May 2024 using a qualitative approach through interviews, observations, documentation, and plant identification. The research sample consisted of community members with knowledge and experience in utilizing medicinal plants, selected using purposive sampling. The results revealed 32 species of medicinal plants belonging to 20 families, with leaves being the most widely used plant part. The collected data were then developed into a booklet and validated by material and media experts. Validation results showed an average score of 94.77%, categorized as highly valid, indicating that the booklet is feasible for use as a biology learning medium. The study concludes that a local wisdom-based booklet can serve as an effective and contextual educational tool while supporting the preservation of traditional knowledge. Future research is recommended to conduct classroom trials to evaluate the effectiveness of the booklet in improving students’ learning outcomes and motivation.